Informal Teaching of Special Theory of Relativity - Jindřiška Svobodová; Jan Novotný; Jana Jurmanová (Karolinum Press, 2017)
In the present Case Study we explore the comprehension levels of relativity theory in prospective science teachers who take the introduction to physics lesson at the Faculty of Education. Special Theory of Relativity multimedia animation was used to illustrate basic relativistic consequences. The effect of it for learning was researched. In the research, a case study was used. Research data were obtained by interviews and using open-ended questions prepared by the researcher.